Quality improvement of printed circuit board: A case study of copper in hole - Vanichchinchai, Assadej; Duantrakoonsil, Wanwisa (Science, Engineering and Health Studies, 2018)
The objective of this research is to reduce defective from copper in drilled hole of printed circuit board by adjusting 1) operating speed and retake rate of drill bit in CNC drilling step, 2) vacuum pressure for copper dust of dust collector in CNC drilling machine, 3) pressure and duration in cleaning step with high pressure ultrasonic and 4) life time of drill bit through uses of quality control circle methodology and simple quality improvement tools. Having adjusted this set of factors as a whole, defective from copper in hole was reduced significantly from 12.81% to 0.66% resulting in higher production capacity from lower defective. For future research, it is suggested to study the impact of individual factor and its most suitable value on copper in hole problem with more sophisticated quality improvement and statistical tools.